FTR allocations to ease transition to nodal pricing: An application to the German power system - Friedrich Kunz; Karsten Neuhoff; Juan Rosellón (Energy Economics, 2016)
A shift from zonal to nodal pricing improves the efficiency of system operation. However, resulting price changes also shift surplus across generation and loads at different locations. As individual actors can lose, they might oppose any reform. We explore how allocation of financial transmission rights can be used to mitigate the distributional impact. The fundamental effects with regard to reference node/hub for FTRs, the share of FTRs to be freely allocated and the metric to determine the proportion of rights allocated are explored. We test the results in a setting based on the hourly modeling of the German power system at nodal representation.
Keywords: L50; L94; Q40; 330; Financial transmission rights; Nodal prices; Congestion management; Electricity; Germany